Comparative analysis of the serological reactivity of individuals with clinical history of malaria using two different ELISA tests - Moreno, Yorleydy Ruiz (2021)
Early diagnosis of malaria reduces disease, prevents deaths, and contributes to decreased malaria transmission. The use of specific and sensitive antigens in the execution of serological diagnostics may have an impact on the transmission of the disease. However, many individuals cannot be easily diagnosed by serological tests due to low levels of antibodies in the serum. Using two different Enzyme-Linked Immunosorbent Assay (ELISA) tests (a commercial and an in-house ELISA), a total of 365 serum samples from individuals with a clinical history of malaria were analyzed. From the serum samples analyzed, 192 (53%) samples from the commercial ELISA and 219 (60%) samples from the in-house ELISA presented positive serological reactivity to malaria. The concordance of the samples tested (n = 365) between both ELISAs was of 67% (n = 242), and with the negative control was 100% (n = 17). We demonstrated that the in-house ELISA showed high antigenic reactivity to Plasmodium falciparum antigens when compared with the commercial ELISA. The degree of concordance of both ELISAs suggested the possibility of existence of other P. falciparum antigens present in the crude extract of P. falciparum that are important in the serological response during malaria infection.